Interdisciplinary treatment algorithm for facial high-flow arteriovenous malformations, and review of the literature - Kansy, Julia Katharina; Bodem, Jens; Engel, Michael; Freudlsperger, Christian; Möhlenbruch, Markus Alfred; Herweh, Christian; Bendszus, Martin; Hoffmann, Jürgen; Kargus, Steffen (Journal of cranio-maxillofacial surgery, 2018)
Introduction - High-flow arteriovenous malformations (HF-AVMs) are congenital vascular malformations. Typical localizations include the face, oral cavity, and extremities. Due to the high recurrence rate of AVM after incomplete resection or embolization, a combination of both therapeutic modalities has become the preferred choice of treatment. Therefore, we have developed an interdisciplinary therapeutic treatment algorithm for facial HF-AVM and performed a systematic review of the literature. - Patients and methods - In a retrospective analysis, all patients who were treated using the interdisciplinary therapeutic treatment algorithm for facial HF-AVM between 10/2010 and 09/2014 were included in the study. Small HF-AVMs (n = 2) without prior therapy and with clearly detectable arterial blood supply were treated by surgical monotherapy. Larger, previously unsuccessfully treated HF-AVMs and lesions with complex arterial blood supply were treated using a combined therapy (n = 6). Combined therapy consisted of a preoperative embolization and a subsequent surgical resection 1-2 days later. If an extensive surgical reconstruction became necessary due to the size of the malformation, or the risk of recurrence was high due to the complex vascular anatomical situation, a second postoperative angiogram was performed to safely exclude a residual nidus, using a ‘second look’ prior to definitive wound closure (n = 3). HF-AVMs that did not allow for curative therapeutic intervention due to their size and localization were treated by interventional monotherapy (n = 1). Patients with suspicion of a primarily hormone-dependent growth during pregnancy were closely followed up clinically, following a ‘wait and see’ strategy (n = 1). In addition, a systematic literature review was performed to analyze treatment outcomes and current standards. - Results - 13 patients with a mean age of 39 years were included in the analysis. Patients were followed up for a mean of 26.8 months (range 12-60 months). Combined treatment (n = 9) was free of recurrence in all cases (100%) after a mean follow up of 30.3 months (range 12-60 months). Surgical monotherapy (n = 2) was also successful in both cases. Non-curative, interventional monotherapy lead to significant decrease in symptoms and did not have to be repeated. A postpartum decrease of the tumor could be observed in the ‘wait and see’ group. However, at the end of the observational period, a hormone-independent growth occurred. Results were supported by findings of the review. - Conclusion - The treatment of HF-AVMs of the head and neck remains challenging due to high recurrence rates. In our cohort, following the Heidelberg treatment algorithm both surgical monotherapy and combined surgical and interventional therapy had very high success rates. For non-curative, symptomatic therapy, interventional treatment should be discussed in terms of the risk of growth induction of HF-AVMs. Findings from the literature concerning therapeutic strategies and success rates are in line with the developed Heidelberg treatment algorithm. However, a larger sample of patients will be necessary to prove the validity of this algorithm.